Heterologous Cytomegalovirus and Allo-Reactivity by Shared T Cell Receptor Repertoire in Kidney Transplantation - Stranavova, Lucia; Pelak, Ondrej; Svaton, Michael; Hruba, Petra; Fronkova, Eva; Slavcev, Antonij; Osickova, Klara; Maluskova, Jana; Hubacek, Petr; Fronek, Jiri; Reinke, Petra; Volk, Hans-Dieter; et al. (Frontiers in Immunology, 2019)
Cytomegalovirus (CMV) infection is associated with allograft rejection but the mechanisms behind are poorly defined yet. Although cross-reactivity of T cells to alloantigen and CMV has been hypothesised, direct evidence in patients is lacking. In this observational cohort study, we tested the pre-transplant effector/memory T cell response to CMV peptide pools and alloantigen in 78 living donor/recipient pairs using the interferon-gamma Enzyme-Linked ImmunoSpot (ELISPOT) assay. To prove the hypothesis of cross-reactivity, we analysed by applying next-generation sequencing the T-cell receptor-ß (TCR- ß) repertoire of CMV- and alloantigen-reactive T cells enriched from peripheral pre-transplant blood of 11 CMV-seropositive and HLA class I mismatched patients. Moreover, the TCR-repertoire was also analysed in the allograft biopsies of those patients. There was a significant association between the presence of pre-transplant CMV immediate-early protein 1 (IE-1)-specific effector/memory T cells and acute renal allograft rejection and function (p=0.01). Most importantly, we revealed shared TCR-ß sequences between CMV-IE1 and donor alloantigen-reactive T cells in all pre-transplant peripheral blood samples analysed in CMV-seropositive patients who received HLA class I mismatched grafts. Identical TCR sequences were also found in particular in post-transplant allograft biopsies of patients with concomitant CMV infection and rejection. Our data show the presence of functional, cross-reactive T cells and their clonotypes in peripheral blood and in kidney allograft tissue. It is therefore likely that CMV-donor cross-reactivity as well as CMV specific T-cell elicited inflammation is involved in the processes that affect allograft outcomes.